Germanistik im Beruf: Ausbildung, Karrierechancen, Realität.Spezifik der beruflichen (Fach-)Kommunikation von Germanistenin der Branche moderner Unternehmensdienstleistungen in Polen - Makowski, Jacek (2022)
The goal of this paper is the question of the specificity of professional (specialist) communication of graduates of the German Philology within the branch of modern business services in Poland. The research results presented are based on the global results of the project “The Language Barometer of Łódź 2021. Employees in the Modern Business Services Sector”. The target group in this case are employees of companies in the Polish modern business services sector and, at the same time, graduates of the Master's degree study programme in German Philology at the University of Łódź. The research questions of the survey are primarily directed at the required foreign language skills of the target group, areas of application of foreign languages, the knowledge and specialist areas to be mastered, language training in the company and multilingualism in professional communication.
Keywords: Languages for Specific Purposes; LSP; Business Services; Professional Communication; German; Multilingualism; language didactics; German Philology; Berufskommunikation; Fachkommunikation; Fachsprache; Deutsch; Germanistik